TOURISM STUDENTS’ SOFT SKILLS TOWARD USING ENGLISH IN SMKN 1 PONTIANAK - Riyandani, Rio; Sutapa Y, Y. Gatot; Suhartono, Luwandi (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThe purpose of this study was to find out students’ soft skills level toward using English. The method to conduct this study was case study and the subjects of this research were seven males and seven females of eleventh grade students of Tourism Service Major in SMK  Negeri 1 Pontianak. The result of this study showed that there were 2 students that the total score of the questionnaire were 83 and 85. These results were considered that the students were having Very Good soft sills in both intrapersonal and interpersonal skills. These two students were categorized having more interpersonal skills as well as more social awareness and social skills. There were 12 students whose averages of total scores were 62 to 76 which considered were having Good soft skills. Five of them had more intrapersonal skills as well as self awareness and self skills, while seven of them had more interpersonal skills as well as social awareness and social skills. In conclusion, the students’ average level of soft skills was considered as Good. By recognizing level of students’ soft skills in intrapersonal and interpersonal skills, we are able to decide the suitable activities to develop and maximize their soft skills in tourism service. Keywords: Soft Skills, Tourism Service, Case Study